From consent to institutions: designing adaptive governance for genomic biobanks. - O'Doherty, K; Burgess, M; Edwards, K; Gallagher, R; Hawkins, A; Kaye, J; McCaffrey, V; Winickoff, D (2011)
Biobanks are increasingly hailed as powerful tools to advance health research. The social and ethical challenges associated with the implementation and operation of biobanks are equally well-documented. One of the proposed solutions to these challenges involves trading off a reduction in the specificity of informed consent protocols with an increased emphasis on governance. However, little work has gone into formulating what such governance might look like. In this paper, we suggest four general principles that should inform biobank governance and illustrate the enactment of these principles in a proposed governance model for a particular population-scale biobank, the British Columbia (BC) Generations Project. We begin by outlining four principles that we see as necessary for informing sustainable and effective governance of biobanks: (1) recognition of research participants and publics as a collective body, (2) trustworthiness, (3) adaptive management, and (4) fit between the nature of a particular biobank and the specific structural elements of governance adopted. Using the BC Generations Project as a case study, we then offer as a working model for further discussion the outlines of a proposed governance structure enacting these principles. Ultimately, our goal is to design an adaptive governance approach that can protect participant interests as well as promote effective translational health sciences.